Improving wildfire management outcomes: shifting the paradigm of wildfire from simple to complex risk. Issue 5 (16th April 2023) - Essen, Maureen; McCaffrey, Sarah; Abrams, Jesse; Paveglio, Travis
Abstract : Numerous wildfire management agencies and institutions rely primarily on simple risk approaches to wildfire that focus on technical risk assessments that do not reflect the complexity of contemporary wildfire risk. This review paper argues that such insufficiently complex conceptualizations of risk, which do not account for the social and ecological diversity of fire-prone areas, are key contributors to the continued wildfire dilemma. We discuss distinctions between approaching wildfire as a simple and a complex risk and illuminate the need for expanded and complimentary ways to further fire adaptation. We then share five principles to guide approaching wildfire as a complex risk to increase adaptation to and coexistence with wildfire. Such efforts are more likely to yield socially relevant and legitimate strategies for building wildfire adapted communities by recognizing and accounting for the complexities of wildfire governance amongst a variety of stakeholders who may operate at various scales using different knowledge systems.